hMSCs suppress neutrophil-dominant airway inflammation in a murine model of asthma - Hong, Gyong Hwa (Exp Mol Med, 2017)
Although chronic eosinophilic inflammation is a common feature in patients with asthma, some patients have neutrophil-dominant inflammation, which is known to be associated with severe asthma.Human mesenchymal stem cells (hMSCs) have shown promise in treating various refractory immunological diseases. Thus, hMSCs may represent an alternative therapeutic option for asthma patients with neutrophil-dominant inflammation, in whom current treatments are ineffective. BALB/c mice exposed to ovalbumin and polyinosinic:polycytidylic acid (Poly I:C) to induce neutrophilic airway inflammation were systemically treated with hMSCs to examine whether the hMSCs can modulate neutrophilic airway inflammation. In addition, cytokine production was evaluated in co-cultures of hMSCs with either anti-CD3/CD28-stimulated peripheral blood mononuclear cells (PBMCs) obtained from asthmatic patients or cells of the human bronchial epithelial cell line BEAS-2B to assess the response to hMSC treatment. The total number of immune cells in bronchoalveolar lavage fluid (BALF) showed a dramatic decrease in hMSC-treated asthmatic mice, and, in particular, neutrophilic infiltration was significantly attenuated. This phenomenon was accompanied by reduced CXCL15 production in the BALF. BEAS-2B cells co-cultured with hMSCs showed reduced secretion of IL-8. Moreover, decreased secretion of IL-4, IL-13 and IFN-γ was observed when human PBMCs were cultured with hMSCs, whereas IL-10 production was greatly enhanced. Our data imply that hMSCs may have a role in reducing neutrophilic airway inflammation by downregulating neutrophil chemokine production and modulating T-cell responses.